1994
DOI: 10.1084/jem.180.2.641
|View full text |Cite
|
Sign up to set email alerts
|

Control of rat natural killer cell-mediated allorecognition by a major histocompatibility complex region encoding nonclassical class I antigens.

Abstract: The ability of natural killer (NK) cells to eliminate normal allogeneic hemic cells is well established in several species including mice, rats, and humans. The controlling elements for NK susceptibility in these species map to the major histocompatibility complex (MHC), but in contrast to findings in mice and humans, the mode of inheritance is not always recessive in rats. This finding is not easily explained by the missing self and hemopoietic histocompatibility (Hh) models for NK recognition, and has led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 39 publications
4
79
0
Order By: Relevance
“…In contrast, ALC studies in rats provided ample evidence for stimulatory NK allorecognition both in vivo and in vitro (8,9), and suggested that rat NK cells express a more potent array of activating receptors directed against several distinct target cell allo-MHC determinants encoded within the nonclassical class Ib RT1-C/E/M region (5,10,18,19). We speculated that, like MHC-binding NK receptors in mice and in humans, these rat NK receptors might be functionally associated with DAP12.…”
mentioning
confidence: 86%
“…In contrast, ALC studies in rats provided ample evidence for stimulatory NK allorecognition both in vivo and in vitro (8,9), and suggested that rat NK cells express a more potent array of activating receptors directed against several distinct target cell allo-MHC determinants encoded within the nonclassical class Ib RT1-C/E/M region (5,10,18,19). We speculated that, like MHC-binding NK receptors in mice and in humans, these rat NK receptors might be functionally associated with DAP12.…”
mentioning
confidence: 86%
“…The generation of Con A lymphoblasts and 4-h 51 Cr-release assay was performed as described previously [36]. Three micrograms/well of the indicated purified mAb was added to plated effector cells 20-30 min prior to the addition of target cells.…”
Section: Generation Of Effector Cells and Cytotoxicity Assaymentioning
confidence: 99%
“…Cell purity of NKR-P1G + cells used for experiments were 70-95% NKR-P1G + NKR-P1A + NKR-P1F + CD3 − . The effector cells were used in a standard 4 h 51 Cr-based cytotoxic assay as previously described [42]. Target cells were either stably transfected CHO cells expressing Clr2, Clr4, or Clr7 (CHO WT as control) [16], or 293T cells transiently transfected with Clr cDNA inserted in a pBK-CMV expression vector (Stratagene) with EYFP (Invitrogen) inserted into the reading frame, using FuGENE R 6 (Roche) (manufacturer's protocol) (control is transfected with pBK-CMV.EYFP without Clr insertion).…”
mentioning
confidence: 99%